2022
DOI: 10.3389/fonc.2022.902664
|View full text |Cite
|
Sign up to set email alerts
|

EGFR amplification is a putative resistance mechanism for NSCLC–LM patients with TKI therapy and is associated with poor outcome

Abstract: BackgroundLeptomeningeal metastases (LM) have become increasingly common in non-small cell lung cancer (NSCLC) patients who harbor epidermal growth factor receptor (EGFR) mutation treated with EGFR-TKI and are correlated with inferior prognosis. Evidence in prior research demonstrated that EGFR amplification was more likely presented in advanced clinical stages and was associated with worse survival. However, whether EGFR amplification is a prognostic marker in NSCLC–LM is still inconclusive.MethodsThis study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…It has been shown that EGFR amplification in GBM or lung cancer renders tumor insensitive to EGFR-TKIs ( 3 , 17 ), but the underlying mechanism remains largely unclear. Extensive analysis of cancer genomics indicated that amplification of oncogenes or deletion of tumor suppressors often encompasses the neighboring genes, which cooperatively contribute to tumorigenesis ( 13 15 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that EGFR amplification in GBM or lung cancer renders tumor insensitive to EGFR-TKIs ( 3 , 17 ), but the underlying mechanism remains largely unclear. Extensive analysis of cancer genomics indicated that amplification of oncogenes or deletion of tumor suppressors often encompasses the neighboring genes, which cooperatively contribute to tumorigenesis ( 13 15 ).…”
Section: Resultsmentioning
confidence: 99%
“…The reasons that lead to resistance to EGFR-TKIs in GBM are largely unknown, which may include intertumoral heterogeneity, redundancy in signaling pathways, and insufficient brain penetration of the inhibitors due to the BBB ( 3 ). It has been shown that amplification of EGFR renders tumor insensitive to EGFR-TKIs ( 17 ). Our study demonstrates that SEC61G is coamplified with EGFR in GBM and promotes immune evasion, which reveals a mechanism underlying the inefficiency of EGFR-TKIs in EGFR -amplified tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that EGFR amplification was significantly associated with high-grade histology, tumor necrosis, and high tumor content (See S3 Table in S1 File ). EGFR amplification has been reported as a putative resistance mechanism to EGFR-TKIs in patients with leptomeningeal metastases [ 39 ]. However, one study demonstrated that EGFR sensitizing mutations and amplification were associated with better overall survival and progression-free survival in Hispanic patients treated with erlotinib [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…El estado funcional de Karnofsky fue peor (p = 0,02) y la presión del LCR fue mayor (p = 0,006) en los pacientes con amplificación de EGFR que en los que no la tenían. El análisis multivariante mostró que la mediana de SG fue significativamente más corta en pacientes con amplificación de EGFR que en aquellos que no la tenían, convirtiéndose en un factor pronóstico independiente para una SG (8,3 frente a 15 meses; p = 0,017) (182). Estos hallazgos apoyan nuestra teoría de que la amplificación del gen EGFR en pacientes con CPCE confiere un peor pronóstico y afecta negativamente la supervivencia de estos pacientes.…”
Section: Valor Pronóstico De Las Alteraciones Cromosómicas En El Cpceunclassified